THE USE OF CORPORATE COMMUNICATION EFFORT TO MAINTAIN A GOOD CORPORATE BRAND, BRAND IDENTITY, AND CORPORATE REPUTATION IN RESTAURANT OUTLETS - H. Pand, Regina Pinasthika; Kartikawangi, Dorien (Jurnal InterAct, 2018)
This study examines about corporate brand and corporate identity that will succeed if the company does branding along with corporate communication effort of the company. This company is a F&B business that has been running in the past few years in several cities and already has four outlets; located at Jakarta, Bali, and Yogyakarta. The first restaurant has been running for three years; began the business with ‘degustation’ private dining restaurant which is already expanded to casual dining restaurant in late 2015. This company already has brand identity and reputation in Jakarta and wants to maintain the brand identity and reputation in the other outlet of this company in Yogyakarta. The target market of the company is middle up to level A+, because this company wants to maintain regular clients that this company already have in all outlets. Moreover, brand identity of the restaurant is classy, elegant, Spanish authentic restaurant, and has a grade A quality. This study used literature review as a research method. With the tools of corporate communication by Hatch, Schultz, and Larsen (2001); brand identity and reputation of the restaurant in Jakarta will be implemented in Yogyakarta’s branch; which is already open for public last July. Given the difference of culture and region with Jakarta, it’s seen that some differences may apply to standard and perception to brand identity and reputation in Yogyakarta. Therefore, this research will discuss how to make these four things applicable in Yogyakarta by not reducing information and/or standard in Jakarta, by corporate communication effort.